Critical Hypomagnesemia and Seizure Induced by Chronic Use of Proton Pump Inhibitors (PPIs) (Translation: The University of Toledo Journal of Medical Sciences, 2019)
Background: Chronic use of proton pump inhibitors (PPIs) may lead to severe hypomagnesemia, although it is a rare side effect. Hypomagnesemia related to PPIs use less reported compared to other side effects. Critically low magnesium level may lead to fatal seizure activity, which could lead to death if went undiagnosed. Case presentation: This is a report of a 49 yearold female with a history of gastroesophageal reflux disease (GERD) presented to our emergency department with a seizure activity and critically low magnesium level (< 0.5 mg/dL). Initially the patient was hemodynamically unstable, required intubation, and admitted to the medical intensive care unit (MICU). After further management in MICU, patient stabilized and transferred to the inpatient regular medical floor. Most of the potential common causes of her low magnesium level were thoroughly investigated and ruled out except for PPIs use (as she was a chronic user). The patient was advised to discontinue her PPIs and to use alternative medications because of lifethreatening side effect "hypomagnesemia"and based on the riskbenefit balance (as the risk overweight the benefits in this situation). No further hypomagnesemic episodes reported after the second admission to the ICU unit when PPIs were discontinued completely. Conclusion: Although PPIs use is beneficial for patients with GERD especially those with gastritis, but may lead to lifethreatening hypomagnesemia in rare occasions. Physicians should be aware of this side effect in all patients with chronic PPIs use. In addition, we recommend that patients who developed this rare side effec need to use alternative medications to prevent recurrence an fatal consequences. Further research is needed to determine the incidence and the association between the development of hypomagnesemia and the use of different types of gastric acid suppressants.
Keywords: PPIs; hypomagnesemia; seizure